Silver nanoparticle Bacteriostatic activity Assessment against Extended-Spectrum Beta-Lactamase Producing Uropathogenic Klebsiella pneumonia (Raparin Journal of Humanities (RJH), 2020)
The aims: Screen for the Extended-Spectrum Beta-Lactamase producing Klebsiella pneumonia from urinary tract infection UTI patients phenotypically and molecularly, also testing different sizes of silver nanoparticles as antibacterial for the resistance isolates. Methodology: Vitek Extended-Spectrum Beta-Lactamase test , molecular confirmed ESBL-producing isolates were checked by PCR for the presence of AmpC and blaCTX-M genes. Flat well microtiter plates were used for packing of antibacterial activity of silver nanoparticles . This study included 85 urine samples were collected from patients that admitted to the "Rizgary Hospital" in Erbil province from 15 June to 15 December 2018. Antibiotic sensitivity test of all isolates to (Ampicillin, Ampicillin/sulbactam Cefazolin, Ceftazidime Ceftriaxone, Cefepime, Imipenem, Nafcillin and Nitrofurantoin )antibiotics were tested by the disc-agar method as standardized by the National Committee for Clinical laboratory Standards (2006).Results: Out of 51 tested isolates of Klebsiella pneumonia, 11 (21.6%) were Extended-Spectrum Beta-Lactamase Producers. Their antibiotic resistance profile showed the rate of resistance isolates was (100%) to Ampicillin, Cefazolin, Ceftazidime and Ceftriaxone and ( 90%) to Cefepime .In addition the susceptibility to Imipenem was (72.7%) of isolates. The bands of the AmpC and bla CTX-M genes was noted in (42.9%) samples and the remain samples (57.1 %)were negative for both genes. The Minimum Inhibitory Concentration during incubation of Non ESBL producer - ESBL producer isolates in series concentrations of silver nanoparticles size (20 nm) was between (625 -2500) µg/ml and for size (90 nm), it was (1250) µg/ml for non ESBL producer and not affected ESBL producer isolates .The increased percentage rates of β-lactamase producing Klebsiella species were seen which was considered as an alarm, due to limitation in treatment options for UTI. It was appeared that Imipenem currently is the main available antibiotic for UTI treatment as a drug of choice. It was noticed that different sizes of silver nanoparticles showed antibacterial activity for ESBL producing isolates.